1997
DOI: 10.1093/geront/37.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Deficit in Alzheimer's Disease: Relation to Caregiver Burden

Abstract: Patients with Alzheimer's disease (AD) show varying degrees of awareness of their deficits. To examine the impact of this phenomenon upon the distress experienced by family caregivers of AD patients, we analyzed caregiver burden in relation to patient awareness of deficit in three different functional domains. The relationship of burden to selected sociodemographic variables was also explored. Results of multiple regression analyses suggested that caregiver burden was associated with impaired patient awareness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
105
1
15

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(129 citation statements)
references
References 12 publications
8
105
1
15
Order By: Relevance
“…Several cross-sectional studies have found anosognosia in people with dementia to be associated with caregiver burden and, to a lesser extent, depression [4][5][6][7][8]. At least two different conclusions may be drawn from these results.…”
Section: Introductionmentioning
confidence: 98%
“…Several cross-sectional studies have found anosognosia in people with dementia to be associated with caregiver burden and, to a lesser extent, depression [4][5][6][7][8]. At least two different conclusions may be drawn from these results.…”
Section: Introductionmentioning
confidence: 98%
“…The lack of a gold standard for defining and detecting anosognosia has led to several different instruments being developed to assess it [17,32,33], and this makes it difficult to compare our results with previous studies. Starkstein et al also used the AQ-D in a longitudinal study and reported an accumulated incidence rate much lower than ours (21% versus 38%) [34].…”
Section: Discussionmentioning
confidence: 93%
“…Although anosognosia is associated with cognitive impairment, it may also be present in the early stages of the disease (between 25.7% and 38.5% of patients with mild dementia present with anosognosia), where it has worse repercussions for both patients and caregivers [7,[15][16][17]. Currently, however, there is no biological marker or gold standard for detecting anosognosia, and several instruments have been developed [11,18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La presencia de altos niveles de sobrecarga en el cuidador asociada a la presencia de anosognosia puede influir en la valoración objetiva de las capacidades de los pacientes e incrementar la discrepancia entre paciente y cuidador 34,35 . La valoración de la calidad de vida, un factor importante en la evaluación de tratamientos, también presenta alteraciones asociadas a la presencia de anosognosia 27,28 .…”
Section: Discussionunclassified